SELEÇÃO DE FORNECEDORES DE MATERIAIS NA CONSTRUÇÃO CIVIL - Gomes, Maria Micheline Barreto; Campos, Vanessa Ribeiro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Selection of suppliers has played an increasingly significant role in the purchasing department of a construction company, since the correct choice of a supplier can reduce production costs and helps to increase de quality of services or product. Hence, the selection process of suppliers must consider several criteria that involve quantitative and qualitative aspects. The aim of this study is to propose a methodology for the selection of materials suppliers. Among the types of materials suppliers were ceramics, cement and others based on the ABC curve. The development of the a multi-criteria analysis model was based in a case study in a construction company operating in the city of Fortaleza / CE and in Juazeiro do Norte / CE. The PROMETHEE II method applied to obtain the hierarchy of the suppliers. This methodology allows a careful analysis in the choice of suppliers and contributes to the improvement of managers' decision-making. In this study, the quality of the product was increased and one of the main parameters that needed improvement was flexibility of payment.